DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS WITH THE USE OF INFORMATION TECHNOLOGIES - Khamdamova Nozima Muqimovna (Journal Park Publishing, 2022)
Robotics is a science-intensive industry. Success in its development depends on progress in other areas of technical knowledge, as well as progress in fundamental sciences [1, p. 95]. Based on modern scientific and technological achievements, studying the interaction of robotic systems and people, creating new embedded sensors and sensor networks, developing new human-machine interfaces, including new ways to use gestures and voice interfaces to control computer and robotic systems, etc. the task is set.
Keywords: technical creativity, technique, technology, modern tool, elements of robotics, Arduino board.